NON-ADHERENCE FACTORS TO TUBERCULOSIS TREATMENT IN PULMONARY TUBERCULOSIS PATIENTS IN SURAKARTA CENTRAL GENERAL HOSPITAL, INDONESIA - Hidayah Karuniawati; Gayuh Ilham Rahmadi; Erindyah Retno Wikantyasning (Jurnal Farmasi Sains dan Praktis, 2023)
Tuberculosis is an infectious disease that must be treated in the long term. One of the therapeutic efficacy factors in tuberculosis treatment is medication adherence by patients. Non-compliance to treatment leads to no achievement of treatment goals, increasing the risk of resistance, mortality, and morbidity. This study analyzed association factors that predicted the influence of the pulmonary tuberculosis patient’s non-adherence to anti-tuberculosis medicines in Surakarta Central General Hospital, Indonesia. The research was analytical research with a cross-sectional approach. The study samples were 80 respondents. The inclusion criteria were patients diagnosed with pulmonary tuberculosis in Surakarta Central General Hospital, aged >17 years old, and patients who received Anti-Tuberculosis Drugs for at least two months. This study used a questionnaire that has been validated. Data were analyzed by bivariate analysis (chi-square or Fisher) and continued by multivariate logistic analysis. Of 80 respondents, there were 30 respondents (37.5%) were non-adherence to taking Tuberculosis (TB) drugs. The predicted factors that influenced non-adherence in taking anti-tuberculosis drugs were beliefs about the medicine of the harm subscale (p = 0.001; OR = 8.167), suffering from drug side effects (p = 0.022; OR = 4.222), and beliefs about the medicine of overuse subscale (p = 0.038; OR = 3.504). The wrong beliefs of patients and side effects may influence patients’ adherence to TB medicines. Counseling and education are needed to improve patients’ beliefs and manage medicines’ side effects.